QUALITY OF PUBLIC SERVICES IN POPULATION ADMINISTRATION AT THE POPULATION AND CIVIL REGISTRATION AGENCY OF SIJUNJUNG REGENCY - Reni Afsoni; Maria Ekowati (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2026)
Population administration services constitute a fundamental service directly linked to the fulfillment of citizens' civil rights. This research addresses the issues of lengthy service processes and long waiting times at the Sijunjung Regency Population and Civil Registration Agency (Disdukcapil), compounded by the region's vast geography and uneven population distribution across its *nagari* (villages). The study examines three questions: (1) the quality of population administration services at Disdukcapil Sijunjung regarding the responsiveness and reliability dimensions of the SERVQUAL theory; (2) the factors contributing to slow service processes and long waiting times; and (3) relevant, evidence-based improvement strategies aligned with Law No. 25 of 2009. The research employs a literature study method, reviewing scholarly literature, official government reports, applicable regulations, and relevant empirical data. The study concludes that: first, regarding responsiveness, services at Disdukcapil Sijunjung remain reactive rather than proactive, driven by the lack of a structured queuing system, limited public access to procedural information, and the staff's inability to anticipate peak service demand periods. Second, service delays and unresponsiveness stem from the interplay of five factors: limited human resource capacity, inadequate information technology infrastructure, the region's vast and dispersed geography, low digital literacy among the population, and a service system design that lacks a user-oriented approach. Third, recommended solutions include implementing a digital queuing system, strengthening IT infrastructure and contingency procedures, standardizing and disseminating public service protocols, conducting outreach services (*jemput bola*) in remote areas, and launching digital literacy programs tailored for *nagari* communities.